Against the grain : the British far left from 1956 - Smith, Evan, 1981-; Worley, Matthew (Manchester University Press, 2014)
'Against the grain' is the first general history of the British far left to be published in the twenty-first century. Its contents cover a range of organisations beyond the Labour Party, bringing together leading experts on British left-wing politics to examine issues of class, race and gender from 1956 to the present day.--page 4 of cover.